2020
DOI: 10.1093/ejo/cjaa024
|View full text |Cite
|
Sign up to set email alerts
|

Relapse 1 week after bracket removal: a 3D superimpositional analysis

Abstract: Summary Objectives To measure tooth movement 1 week post-treatment and assess potential correlation with changes invoked during treatment. Subjects and methods Thirty-eight patients were recruited (19 males, 19 females). Polyvinyl siloxane impressions were taken after bracket debonding (T1) and 1 week later (T2) and digitally scanned. During this period no retention was used. The digital cast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Registration of maxillary dental models has mostly been reported in the permanent dentition 6,7,9‐13,16,18‐20 . Some studies reported the use of these methods in growing patients 8,14,15,17,20 . However, this is the first study evaluating the registration methods in growing patients after treatment of anterior open bite, which poses clinical challenges to quantify vertical changes over time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Registration of maxillary dental models has mostly been reported in the permanent dentition 6,7,9‐13,16,18‐20 . Some studies reported the use of these methods in growing patients 8,14,15,17,20 . However, this is the first study evaluating the registration methods in growing patients after treatment of anterior open bite, which poses clinical challenges to quantify vertical changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…The first approach requires identification of anatomical landmarks, [9][10][11]14,16,18,19,35 and the surface-based approach requires identification of regions of interest (reference area). [6][7][8][12][13][14][15]17,19,20,30,35 A consensus regarding the ideal method for registration has not been established yet. 21 Registration of maxillary dental models has mostly been reported in the permanent dentition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is important, since inaccurate prediction of tooth movements might be associated with prolonged duration of aligner treatment with an additional need for refinement strategies. Patient burnout and, most likely, increased potential for relapse tendency are further concerns (Papagiannis et al, 2021;Vagdouti et al, 2019;Vagdouti and Koletsi, 2020).…”
Section: Introductionmentioning
confidence: 99%